Purity analysis of nine pesticides collected from eight locations in Bangladesh - Begum, Afroza; Akon, MW; Ahmed, MS; Alam, SN (Bangladesh Journal of Agricultural Research, 2016)
The study was undertaken to determine the purity of available marketed brands of nine selected pesticide groups viz., chloropyriphos, diazinon, carbofuran, pyrazosulfuranethyle, dimethoate, cypermethrin, carbendazim, mencozeb and quinalphos. These pesticides were collected from local markets of eight locationsviz., Rajshahi, Rangpur, Dinajpur, Bogra, Chittagong, Mymensing, Comilla, Norshingdi and Jessoredistricts of Bangladesh where extensive usage of pesticides was recorded. Among the 66tested pesticides, 66.66 % (44 in number) were found ?90% pure in terms of active ingredient (AI). The purity range of about 12% of the total tested brands was 80%--90%. And the remaining 21.34% were less than 80 % pure, of which three pesticide brands contained no active ingredient (AI) at all. Bangladesh J. Agril. Res. 41(4): 685-694, December 2016